Aniline Process Creation for Conversion Improvement Using Hydrogenation Process - Rohmah, A'ida Noor; Palupi, Agnes Retno; Manullang, Amanda Nathalia Harti Marusaha; Erawati, Hadasa Dyah Budi (Journal of Chemical Engineering Research Progress, 2025)
The hydrogenation process of nitrobenzene to aniline is one of the main methods in the chemical industry to produce aniline with high efficiency. This research focuses on optimizing this process through system modification, which includes implementing a recycling flow and adjusting operating conditions such as temperature and pressure. The simulation results show an increase in the conversion of nitrobenzene to aniline by 1.44% after modification, from 96.82% to 98.26%. Although these improvements may seem small, their impact is significant on an industrial scale, especially in reducing raw material waste and energy consumption, making it a more sustainable solution. This study provides valuable insights for improving the efficiency of aniline processes in the context of the global chemical industry. Copyright © 2025 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).